(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This paper aims to reveal of the major factors that affecting e-government implementation and obstacles facing it, through a comprehensive review of previous studies in this field covering different regions with diversity in cultural and economic backgrounds. Also, this article shows the stages that e-government get through to full implementation, highlighting the degree of e-government in various countries, depending on E-Government Development Index (EGDI). Finally, the paper finds that it is not a precondition to be a developed country to be in the higher levels of EDGI classification, but in other hand all countries in low-EDGI level group belongs to least developed countries and those exposed to widen divide between people who have access to the Internet and online services and those who do not.